Note sur la notion d’échelle dans la géographie française de la fin du XIXe siècle et du début du XXe siècle - Marie-Claire Robic (Cybergeo, 2004)
In French geography at the end of the nineteenth century, little reflection was devoted to the notion of scale. It figured, however, in debates related to the pedagogical and political enterprise, or to the epistemological specificity of the discipline, or, finally, to the principles governing the dividing up of the world.